Assertive Community Treatment For People With Alcohol Dependence: A Pilot Randomized Controlled Trial. (9th December 2016) - Drummond, Colin; Gilburt, Helen; Burns, Tom; Copello, Alex; Crawford, Michael; Day, Ed; Deluca, Paolo; Godfrey, Christine; Parrott, Steve; Rose, Abigail; Sinclair, Julia; Coulton, Simon
Abstract: Aims: A pilot randomized controlled trial (RCT) to assess the feasibility and potential efficacy of assertive community treatment (ACT) in adults with alcohol dependence. Methods: Single blind, individually randomized, pilot RCT of 12 months of ACT plus treatment as usual (TAU) versus TAU alone in adults (age 18+ years) with alcohol dependence and a history of previous unsuccessful alcohol treatment attending specialist community alcohol treatment services. ACT aimed to actively engage participants for 12 months with assertive, regular, minimum weekly contact. ACT was combined with TAU. TAU comprised access to the full range of services provided by the community teams. Primary outcome is mean drinks per drinking day and percent days abstinent at 12 months follow up. Analysis of covariance was conducted using 80% confidence intervals, appropriate in the context of a pilot trial. Results: A total of 94 participants were randomized, 45 in ACT and 49 in TAU. Follow-up was achieved with 98 and 88%, respectively at 12 months. Those in ACT had better treatment engagement, and were more often seen in their homes or local community than TAU participants. At 12 months the ACT group had more problems related to drinking and lower quality of life than TAU but no differences in drinking measures. The ACT group had a higher percentage of days abstinent but lower quality of life at 6 months. The ACT group had less unplanned healthcare use than TAU. Conclusions: An trial of ACT was feasible to implement in an alcohol dependent treatment population. Trial registration: ISRCTN22775534